SCIENTIFIC APPROACHES TO THE STUDY OF THE CATEGORY “REPUTATION” - Shkromyda , V.V. (The actual problems of regional economy development, 2018)
The relevance of the study of the essence of «reputation» of personality and enterprise in both social and economic life of the present is presented. Established in the specialized literature, there are a variety of scientific approaches to the study of the category of “reputation”, in particular psychological, sociological, political, legal, and economic. It is determined that the scientific research approaches presented are characterized by a multidirectional understanding, which ultimately allows, on the basis of a disciplinary connection, to more accurately outline the theoretical facets of such a phenomenon as “reputation”, to distinguish existing properties in relation to formation and to develop recommendations in the direction of its use in perspective in order to achieve the set tasks.